Some Relations on Different Types of Splicing Systems - Yuhani, Yusof; Nor Haniza, Sarmin; Fong, Wan Heng; Fariba, Karimi (Universiti Teknologi Malaysia, 2011)
Splicing system is a formal characterization of the generative capacity of specified enzymatic activities acting on initial DNA molecules that was first initiated by Head in 1987. This splicing system is formally llustrated under the framework of Formal Language Theory which is a branch of Theoretical Computer Science and Applied Discrete Mathematics. There are many types of splicing systems including null-context, simple, semi-simple and seminull. In this paper, some relations for those types of splicing systems are presented.